Low-Frequency Magnetic Field Exposure System for Cells Electromagnetic Biocompatibility Studies - Zuzana Judakova; Ladislav Janousek; Roman Radil; Lucia Carnecka (Applied Sciences, 2022)
The advancement in science and technology has resulted in the invention and widespread usage of many electrical devices in the daily lives of humans. The exponential use of modern electronic facilities has increased electromagnetic field exposure in the current population. Therefore, the presented article deals with designing, constructing, and testing a new applicator system developed for cells electromagnetic biocompatibility studies. The applicator system is intended for studying the non-thermal impacts of low-frequency magnetic field on cell cultures growth. Main attention is focused on increasing the capacity of the applicator and effectivity of the experiments. The key idea is to reach high level of the magnetic field homogeneity in an area of interest and the temperature stability during the biocompatibility studies. The applicator system is designed based on numerical simulations and its construction, measurements, and properties evaluation are also reported for proving the applicator’s functionality. The new applicator allows performing five parallel experiments at the same time under the same conditions. The simulation together with the experimental results confirm that the magnetic field homogeneity reaches 99% in the area of interest and the maximum temperature instability is lower than 2% during the experiments. The effectiveness of new applicator is tested and proved during preliminary experiments with Saccharomyces Cerevisiae cells. The observed effects of MF exposure represent maximal stimulation of 74% and maximal inhibition of 49%. The reason why MF with the same parameters induces inhibition in one sample and stimulation in the other will be the subject of further research.